A green and resilient supply chain design model. (10th December 2020) - Das, Kanchan
Green supply chain factors and practices have gained increasing attention from the customers, businesses, and academicians for improving overall business sustainability. Because customers also value reliable business performance in terms of product and services availability, supply chains must be resilient for their sustainability and business continuity. Supply chain (SC) operations are exposed to various internal disasters initiated by humans and external disasters from natural calamity and terrorist activities. This research designs a SC model that incorporates green approach-based product design, procurement, manufacturing, and distribution management. The model also includes resilience planning for these supply chain steps. The objective of the research is to improve overall sustainability performance of the supply chain by integrating contributions of green factors and resilient criteria in all phases of a supply chain. A numerical example illustrates applicability of the model, overall approach of the study, and managerial insights.